TOURISM PRODUCT QUALITY PERCEPTIONS AND BIG SPENDERS’ TRAVEL INTENTIONS IN MALAYSIA: A COMPARATIVE STUDY OF SOUTHEAST ASIAN AND MIDDLE EASTERN COUNTRIES - Zainuddin, Zaliha; Mazni, Saad; Ong, Mohd Hanafi Azman (Penerbit UMT, 2021)
Tourism is the second-largest economic driver of the Malaysian economy. This paper aims to examine the mediating role of perceived tourism product quality (TPQ) in Malaysia on electronic word-of-mouth (eWOM) and the intent to travel to Southeast Asia (SEA) and the Middle East. Two-fold objectives were developed which are to investigate the significant difference of the perception between SEA and Middle East countries on Malaysian’s tourism products quality and to examine the mediating role of perceived tourism products quality in Malaysia towards eWOM and travelling intentions of SEA and the Middle East. The questionnaire that was used to collect the data used in this study was designed with tourists from SEA and the Middle East who have been to Malaysia in mind. The questionnaire was designed for online distribution using Google Forms. The study processed 92 responses from Middle Eastern tourists and had another 79 respondents from SEA. The data sets and responses were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) and MANOVA techniques. The findings show a significant mediating effect of perceived TPQ towards the eWOM and revisit intentions of tourists. Besides, comparison analysis shows that SEA tourists are more likely to revisit Malaysia than the Middle East, the same as for the finding of eWOM and perceived TPQ. TPQ has a mediating impact on eWOM and the intention to revisit both geographical locations. The findings of this study are expected to positively affect stakeholders, especially the State Tourism, Tourism Board, and tourism industry players.